Strategic signaling and new technologically superior product introduction: a game-theoretic model with simulation - Madjid Tavana; Debora Di Caprio; Francisco J. Santos-Arteaga (Technological and Economic Development of Economy, 2018)
User acceptance of technology is essential to determine its success. The current paper incorporates the main properties of the technology acceptance models (TAMs) developed by management scholars into a pre-commitment signaling duopolistic framework, where two competing firms must decide the level of technological improvement of the products being introduced. As a result, the corresponding equilibria of the duopolistic technological games will be determined by demand-based factors, providing a novel approach and complementing the current supply-based economic and operational research models developed in the literature. The proposed model will be simulated numerically to illustrate the strategic optimality of the update process of smartphone and tablet characteristics defined by Apple and Samsung as the market developed.